CCAFS and the Healthy and Sustainable Food Systems Network at the Columbia University Climate School - CGIAR Research Program on Climate Change, Agriculture and Food Security; Columbia University (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Throughout 2021, CCAFS partnered with the Healthy and Sustainable Food Systems Network at Columbia University on several events intended to arise ambition around climate and food systems, especially in the run-up to the 2021 UN Food Systems Summit and COP26. The Healthy and Sustainable Food Systems Network is focused on combating the main challenges of agriculture and food systems. One of their main goals is engaging faculty, researchers, and students from across Columbia in order to bring areas like nutrition and health, climate, economics, human behavior, policy, equity and vulnerability together. The work is expected to contribute to the establishment and development of the food-related themes of the Columbia Climate School, as well as support the university’s goal to “bring knowledge and experts to the world and solve real world problems.”